2016
DOI: 10.1097/fbp.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Dose and elasticity of demand for self-administered cocaine in rats

Abstract: The present experiment tested whether the elasticity of demand for self-administered cocaine in rats is dose-dependent. Subjects lever pressed for three different doses of intravenous cocaine – 0.11, 0.33, and 1.0 mg/kg/infusion – on a demand procedure where the number of lever presses required per infusion increased within a session. The main finding was that demand for the 0.11 mg/kg dose was more elastic than it was for the two larger doses. There was no difference in demand elasticity between the 0.33 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Winger et al (1993, 2006) tested three cocaine doses in monkeys and found that demand elasticity for the two larger doses did not differ, but demand for the lowest dose was more elastic. Kearns and Silberberg (2016) tested three doses of cocaine – 0.11, 0.33, and 1.0 mg/kg – in rats and found that elasticity of demand did not differ for the two larger doses. Demand for the small dose (near to the smallest dose that still acts as a reinforcer) was more elastic than was demand for the other doses.…”
Section: Discussionmentioning
confidence: 99%
“…Winger et al (1993, 2006) tested three cocaine doses in monkeys and found that demand elasticity for the two larger doses did not differ, but demand for the lowest dose was more elastic. Kearns and Silberberg (2016) tested three doses of cocaine – 0.11, 0.33, and 1.0 mg/kg – in rats and found that elasticity of demand did not differ for the two larger doses. Demand for the small dose (near to the smallest dose that still acts as a reinforcer) was more elastic than was demand for the other doses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that the elasticity of rats’ demand for cocaine was independent of dose when using doses above a minimum threshold. Kearns and Silberberg (2016) tested elasticity of demand for three doses of cocaine (0.11, 0.33, and 1.0 mg/kg/infusion), and found that demand elasticity was equivalent for the two higher doses, but demand was more elastic for the lower dose (which was near the lowest dose that is still reinforcing in rats). A similar result has also been found in monkeys responding for cocaine (Winger 1993; Winger et al, 2006).…”
Section: Discussionmentioning
confidence: 99%